FAMILY'S INFLUENCE ON THE MAJOR CHARACTER'S PERSONALITY DEVELOPMENT IN BARBARA CARTLAND'S A HAZARD OF HEARTS: A BEHAVIORIST APPROACH - KILBAREN, INDRIWATI (2007)
The major problem of this study is how the family influences the major character's personality development based on behaviorist approach. So, the study focuses on the major character, namely Serena Staverly. In this research the writer employs the qualitative method. In this method, she uses two data sources, namely primary data and secondary data sources. The primary data source is the novel itself. The secondary data sources are the books about behavior, some books about personality and also the other sources, which are related to the analysis. The method of data collection is literary research and the technique of data collection is descriptive technique. Based on the analysis, the outcome of this study shows that the problems faced by major character is influenced by her family. The influences that they give not only positive influence but also negative influence. All the stimuli are responded by her in the form of her attitude and behavior. She takes the values learned from all the influences that the family gives to her and those values influence her personality development. Therefore, she tries to choose the best values that she learns from her family to make her life better.